Pilot development of innovation scales for beverage manufacturing companies in a developing country - Marcia Nathai-Balkissoon; Chris Maharaj; Rafael Guerrero; Rydell Mahabir; Isaac Dialsingh (Cogent Business & Management, 2017)
Innovation can enhance economic success for companies and countries alike. This study identified innovation drivers for beverage manufacturing companies in the developing nation, Trinidad and Tobago (T&T). Factor analysis using principal components analysis was applied to self-reported data from 14 beverage manufacturers, organising 10 influencing variables into 3 components that impacted on the companies' innovation. Component 1 addresses the role of company acquisitions, customer feedback and employee feedback regarding product improvements, Component 2 deals with the value of same-industry company collaborations and new ideas proposed by managers or customers and Component 3 focuses on supporting research and development through industrial park tenancy, hiring R&D personnel and higher education collaboration. Findings are discussed in the context of several characteristics of innovation in T&T, including the observed tendency of companies to practice incremental as opposed to radical innovation. Management recommendations to boost innovation include leveraging government policies, developing external collaborations, making management systems more innovation-focused, enhancing employees' innovation competencies, focusing on actively generating new ideas to drive radical innovation and embedding innovation targets and performance measures into routine operations. Prospects for further research include studying how innovation is supported or hindered by within-industry collaboration in developed vs. developing countries.
Keywords: 650